Research on the Connotation,Denotation of the Ground Information Port - Bin ZHOU; Zuoya ZHENG; Linyao QIU; Gang LIU; Zhou LU (天地一体化信息网络)
In view of the existing problems in infrastructure,data sharing,application services and other aspects in China's space information application service system,the defi nition,construction concept and development goal of ground information port (GIP) was proposed by referring to the mature concept of ＆quot;port＆quot; in the fi eld of aviation and transportation.Combined with the construction of the national project of space-integrated-ground network (SIGN),ground information port aims to eliminate information island,get through system channel and eliminate application chimney stress on this basis,from the ＆quot;sharing,integration of general application,open＆quot; concept,the connotation and denotation of the GIP were discussed.It will provide reference for the construction of the national networking spatio-temporal information service system in the future.